Decentralisation and regional cabinet size: the Spanish case (1979–2015). Issue 4 (4th July 2017) - Vall-Prat, Pau; Rodon, Toni
Abstract: This article explores under what conditions regional governments tend to have larger or smaller cabinets. The main contention is that cross-regional variation in cabinet size is partly explained by the dynamics set up by the multilevel system of government, mainly territorial decentralisation, multilevel government (in)congruence or the existence of nationally distinct regions. The hypotheses are tested with a new and original dataset built upon the Spanish case (1979–2015). Findings show that regions with more welfare state policies, especially when the region's economic capacity is high, and nationally distinct regions tend to have bigger executives. In contrast, decentralisation in the form of basic state functions and government incongruence do not have a significant effect. Results have important implications for our understanding of sub-national territorial institutions and their interaction with decentralisation dynamics.